(untitled) (Bangladesh Journal of Microbiology, 2012)
The aim of this study was to isolate and identify uterine microorganisms in postpartum cows and to observe the occurrence of uterine infection in crossbred and local cows. One hundred and nine samples, from both crossbred and local dairy cows were collected from Chittagong area. They were inseminated artificially (n=89) and naturally (n=20). Samples were collected at least 3 months after calving. Among the selected cows, 33 had different reproductive diseases and the rest were from apparently healthy cows. The crossbred dairy cows were more susceptible to reproductive diseases (19.27%) than the local ones. Uterine infection was higher (52%) in cows inseminated artificially than that of natural ones (21.21%). Nineteen different types of bacteria were isolated from both diseased and healthy animals, except Clostridium spp and Nocardia spp which were not found in diseased animal. Likewise, Bacillus spp and Salmonella spp were absent in healthy animals. Most prevalent bacteria in diseased animal were Staphylococcus spp and Streptococcus spp found in 33% and 27.3% of the cases respectively. In non-diseased cases, the highest number of samples was positive for Bacteroied spp (13.2%) followed by Streptococcus spp (10.4%). On average, the highest number of bacterial population was isolated from diseased samples and most of those bacteria are pathogenic. DOI: http://dx.doi.org/10.3329/bjm.v28i1.11804 Bangladesh J Microbiol, Volume 28, Number 1, June 2011, pp 19-23